(untitled) (Indian Journal of Animal Production and Management, 2013)
The present study was conducted on 420 commercial day old broiler chicks of ‘Caribro Dhanraja’ starin to investigate the behaviour performance under two light sources upto 35 days of age. The broiler chickens spent the majority of time in sitting, feeding, foraging, standing, drinking, pecking and walking. During day and night under fluorescent and incandescent light sources all the bahvioral activities have difered significantly. Broiler chickens spent a large proportion of their rime (44-55%) sitting on the litter. This was significantly more under incandescenet than fluorescent light. Time devoted in stand, lie, feed, drink and forage activity was significantly more under fluorescent whereas walk activity was more under incandescent light source. Wingshake, stretch, dustbath and manipulate activity was significantly more under incandescent than fluorescent light where as peck and preen activity was comparatively more in fluorescent light source. Aggression was significantly more in fluorescent light during day time. The birds spent more time in other activities under fluorescent than incandescent light.